OCTREOTIDE AMELIORATES DERMAL FIBROSIS IN BLEOMYCIN-INDUCED SCLERODERMA - Orhan, S. O.; Yolbas, S.; Yildirim, A.; Tektemur, A.; Ozercan, I. H.; Onalan, E.; Koca, S. S. (Bmj Publishing Group, 2015)
[Abstract Not Available]